The Influence of Information and Communication Technology-Based Learning Media on Enhancing Students' Learning Motivation - Muliana Halawa (Jurnal Pendidikan Vokasi Indonesia, 2024)
This study aims to examine the influence of Information and Communication Technology (ICT)-based learning media on enhancing students' learning motivation. A quasi-experimental method with a nonequivalent control group design was employed. The research sample consisted of two classes of secondary school students selected through purposive sampling. The experimental group received instruction using ICT-based learning media, while the control group received conventional instruction without the use of ICT media. Learning motivation data were collected before and after the learning intervention. Data analysis included a normality test using the Kolmogorov-Smirnov Test, which indicated that the data from both groups were normally distributed (p > 0.05). A homogeneity test using Levene’s Test confirmed that the variability of learning motivation between the two groups was homogeneous (p > 0.05). Furthermore, an independent t-test revealed a significant difference in learning motivation between the experimental and control groups (p < 0.05). These findings indicate that the use of ICT-based learning media has a significant positive effect on students' learning motivation. The implications of this study highlight the importance of integrating ICT-based learning media into the educational process to enhance students' motivation to learn.